F(x)=x2-5x+2

Simple and best practice solution for F(x)=x2-5x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x)=x2-5x+2 equation:



(F)=F2-5F+2
We move all terms to the left:
(F)-(F2-5F+2)=0
We add all the numbers together, and all the variables
-(+F^2-5F+2)+F=0
We get rid of parentheses
-F^2+5F+F-2=0
We add all the numbers together, and all the variables
-1F^2+6F-2=0
a = -1; b = 6; c = -2;
Δ = b2-4ac
Δ = 62-4·(-1)·(-2)
Δ = 28
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{28}=\sqrt{4*7}=\sqrt{4}*\sqrt{7}=2\sqrt{7}$
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-2\sqrt{7}}{2*-1}=\frac{-6-2\sqrt{7}}{-2} $
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+2\sqrt{7}}{2*-1}=\frac{-6+2\sqrt{7}}{-2} $

See similar equations:

| -7-8r=47 | | -2x-7=7x+1+6x | | 6y+3+3y+7=13y-10 | | 7p+35=-7(7-7p) | | 8.40-6.8=14.2=6.3o | | y=1.75*44-20 | | (C-4)(x-18)=x(x-14) | | 6y+3+3y+7+13y-10=180 | | x+4x=3+6x | | 7b+5(b—2)=26 | | y=1.75*39-20 | | y=1.75*26-20 | | y=1.75*14-20 | | y=1.75*7-20 | | 210x=1000 | | 19g-5g-12g-g=8 | | 5-10=2+5x | | 1000=2^y | | y=0.50*45+10 | | 7x+6-5x-3-3x+4-2x=-20 | | 3b+4(b+2)=-20 | | y=0.50*36+10 | | 5x-6+2x-9-3x=-123 | | y=0.50*27+10 | | 9x+2x-6-3x+10=68 | | y=0.50*18+10 | | y=0.50*9+10 | | 8(=5x-9)8(5x-9) | | 45-r=27 | | x/7-12=9 | | x=2(360/2x+8) | | y=1.50*49 |

Equations solver categories